1986
DOI: 10.2307/2531245
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Litter Effects on Dose-Response Modeling in Teratology

Abstract: The fitting of dose-response models to teratology data involving littermates in order to generate estimates of teratogenic risk is receiving increasing attention as a potential alternative to the "safety-factor" approach to risk estimation. In this paper, we utilize the beta-binomial distribution to introduce varying degrees of intralitter correlation, and, for purposes of illustration, consider a logistic dose-response model that describes the logit of risk as a straight-line function of ln(dose). The biases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(90 citation statements)
references
References 11 publications
1
89
0
Order By: Relevance
“…They also conducted simulations and found that the dosespecific model with multiple variation parameters led to unbiased estimation of all model parameters, whether the true variance structure was that of single or multiple parameters, whereas the single-parameter model was less robust. These results are similar to those of Kupper, et al (1986), who assumed the beta-binomial distribution for the response number for each litter and a logistic doseresponse model and found that the model with the multiple-intralitter correlation structure produced less biased results than the model that assumed a single-intralitter correlation.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…They also conducted simulations and found that the dosespecific model with multiple variation parameters led to unbiased estimation of all model parameters, whether the true variance structure was that of single or multiple parameters, whereas the single-parameter model was less robust. These results are similar to those of Kupper, et al (1986), who assumed the beta-binomial distribution for the response number for each litter and a logistic doseresponse model and found that the model with the multiple-intralitter correlation structure produced less biased results than the model that assumed a single-intralitter correlation.…”
Section: Introductionsupporting
confidence: 86%
“…This more accurately specified model improves the estimation of important parameters such as the threshold or, in the case of the spline model, the change point. As illustrated in Kupper, et al (1986) and in Hunt and Rai (2007), the model assuming multiple parameters to model response variation leads to negligible bias, whereas under conditions of major differences in dose-specific variation the model with single parameter may lead to extremely biased estimates. Thus, the model that has multiple variation parameters is the general model that should be used.…”
Section: Resultsmentioning
confidence: 99%
“…When varying q (0.05-0.2), the Dirichletmultinomial MLE caused biased estimates. This situation was also noted for the binomial response cases (Kupper et al, 1986;Yamamoto and Yanagimoto, 1988;Car and Portier, 1993).…”
Section: Simulation Resultsmentioning
confidence: 63%
“…Unfortunately, the former approach ignores the litter, while the latter ignores the contribu tions of the individual fetuses within the litters. More recently, investigators have begun to look at methods for taking litter effects into account in the modeling process (42,63).…”
Section: Notedmentioning
confidence: 99%